Long-term results in patients with intracranial aneurismal subarachnoid hemorrhages and their prognosis - Dudukina S.O. (Medičnì Perspektivi)
In 260 patients with intracranial aneurism hemorrhages long-term results were estimated according to Rankin scale 2,5 years after operation. Long-term results by Rankin 0-2 were considered to be “good”, 3-5 were considered to be “bad” ones. Two years after operation 53% of all patients had “good” long-term outcome. Factors negatively influencing long-term outcomes are to be the following: intra-operational aneurism rupture, temporary arterial clipping in the process of operation, complications in the post-operational period, angiospasm according to the transcranial Doppler sonography, angiospasm prevalence, clinicopathologic hemorrhage characteristics “subarachnoid hemorrhage+others”, critical condition according to H-H>1, feminine sex, aneurism location in the forebrain arteria, subarachnoid hemorrhage lesion according to Fisher> II, ischemic heart disease, pathological comorbitidy, ABO blood group – III or IV. “Good” treatment results 2,5 years after treatment are prognosticated in patients with severe invalidity by Glasgo scale (GOS=3) on hospital discharge, in those who didn’t experience ischemic stroke after operation and with severity of condition I or II according to H-H on admission. In patients with GOS-3 on hospital discharge the best long-term results according to Rankin were observed in those treated under hypothermia conditions. Hypertensive disease worsens long-term results according to Rankin even in patients with GOS-5 on hospital discharge. With positive renovation results by Rankin 0 or 1 in the post-operation period (GOS = 5) excellent long-term results are prognosticated, but the best results could be obtained in patients without hypertensive disease under prophylactic hypothermia.